ANALISIS RASIO KEUANGAN TERHADAP FINANCIAL DISTRESS(Studi Pada Perusahaan Manufaktur yang Terdaftar di Bursa Efek Indonesia Periode 2014-2016) - Dwi Trisnawati, 14.05.52.0046; Susilowati, . Yeye (Students' Journal of Accounting and Banking, 2018)
This study aims to test and analyze financial ratios in the form of profitability, liquidity, leverage and financial distress activities. This research was conducted at a manufacturing company listed on the IDX for the period 2014-2016. In this study, researchers used the purpose sampling method and obtained a sample of 305 samples of manufacturing companies listed on the Stock Exchange. The company data was then tested using logistic regression with the SPSS 21 program to explain the relationship between these variables. The type of data used is secondary data. The results of this study indicate that the profitability variable proxied by ROA has a negative effect on financial distress, the variable liquidity proxied by CR and leverage variables proxied by DER has a positive effect on financial distress, while the activity variable proxied by TATO does not affect financial distress. Keywords: Profitability, Liquidity, Leverage, Activities and Financial Distress.